Perspectivas Hermenêuticas: Uma Releitura do Conceito do Yahweh Criador a partir de Isaías 45,14-25. - Silva, Roberto de Jesus (2018)
This work intends to analyze the title of Creator of the heavens and the earth attributed to Yahweh in Isaiah 45, 14-25, as well as to demonstrate that the theology of Yahweh God the Creator in Israel was initiated by the Deutero-Isaiah in the period in which he was exiled in Babylon with his countrymen. We also emphasize in this thesis that the theology of the Creator God, the heavens and the earth, suffered cultural interference from the Babylonian creation narrative known as Enuma Elish. For this, we use the exegetical study, starting from the analysis of the historical, literary and religious context of the Deutero-Isaiah, in order to demonstrate that the title of Creator attributed to Yahweh, had the purpose of clarifying the Jewish community that was exiled in Babylon, that the god Marduk, was not the creator of the heavens and the earth. Therefore we interpret the title of God the Creator attributed to Yahweh by the Deutero-Isaiah prophet, as a denial of this title directed to Marduk by the Babylonians of the Chaldaean dynasty. We demonstrate that in the post-exilic period, the theology of Yahweh, God the Creator went through evolutions, and the second face of this theology must be seen in the literary production Genesis 1,1-2, 4a - 2,4b-25. We have argued that the writers of the two cosmogonic narratives quoted above in the book of Genesis produced these texts in the post-exilic period to re-affirm the theology of Yahweh God the Creator, begun by the prophet Deutero-Isaiah, circa 540 a.C. Finally, we mention that the Creation Psalms 104; 33; 19; 08 and 136 are the third phase of the theology of the Creator God in Israel in the post-exilic period, and in this the psalmists presented some novelties that were not mentioned by the Deutero-Isaiah, such as: Yahweh, the Lord of Creation, Yahweh the God Craftsman who created the heavens with his hands and the creation of Yahweh bound to his hesed - kindness and other themes that were worked out in this thesis.